Occurrence of Alternaria Toxins, Ochratoxin A and Aflatoxins B1 in Green Arabic Coffee (Coffea arabica) in Saudi Arabia: Risk Assessment on HepG-2 Cell Line and Male Albino Rats - Ahmed Hashim Almusallam; Ahmed Mahmoud Ismail (Journal of Global Innovations in Agricultural Sciences)
Arabica coffee (Coffee arabica L.) is among the most popular and widely consumed drinks globally today. The current study aimed to detect and quantify of potential mycotoxins in coffee beans and to investigate their potential risk on HepG-2 human liver cancer cells and male albino rats. Eighteen fully matured coffee beans samples were collected from different geographical locations in Saudi Arabia. Mycotoxins detected and quantified utilizing high-performance liquid chromatography (HPLC). Cytotoxicity of the detected toxins was investigated utilizing the MTT assay method toward HepG-2 cells and male albino rats. Cytotoxic properties of the detected mycotoxins were investigated at doses of 31.25, 62.50, 125, 250 and 500 µg/ml following exposure durations of 24 and 48 h in comparison with control. HPLC analysis revealed the detection of four Alternaria toxins (ALT-Ts) namely Altenuene (ALT), Tenuazonic acid (TA), Alternariol (AOH), and Altenuisol being AOH reported as the frequently detected mycotoxin in 18 coffee beans samples representing 75 % with quantity ranged 0.98 to 8.97 μg/g. OTA was frequently detected (10 samples, 55.5%) in concentrations varied from 0.75 to 9.87 μg/g. In addition, Aflatoxin B1 was also detected with low quantity ranged 0.89 to 3.22 μg/g. Treatment of HepG-2 cell line with combined Alternaria toxins (ALT, TeA, AOH, and Altenuisol), Aflatoxin B1 (AFB1) and Ochratoxin A (OTA) as well as their combination triggered a decline in cell viability that was proportional to the dose administered. The elevated doses (62.50, 125, 250 and 500 µg/ml) notably reduced cell viability and induced cellular damages when contrasted with the lowest dose (31.25 µg/ml) and control. The IC50 for the tested mycotoxins registered for ALT-Ts, AFB1 and OTA as well as their combination were 115.95, 56.68, 59.86 and 31.05 µg/ml after 48 h of exposure. Secreting inflammatory markers (Interleukin-6 (IL-6), interleukin-1β (IL-1β) and COX-2), and oxidative markers (total antioxidant capacity (TAC), glutathione (GSH) and nitrite (NO) were downregulated by all mycotoxins with the highest decrease induced by their mixture. Malonaldehydes (MDA) and TAC were significantly increased by all toxins in treated rats. Hematological results revealed that AFB1, OTA and ALT-Ts-treated rats exhibited a notable decline in hemoglobin (Hb), red blood cells (RBCs), white blood cells (WBCs), and packed cell volume % (PCV). However, single and double dose-treated rats with OTA, Mix1 and Mix2 exhibited a marked increase in WBCs. The results demonstrated a notable decline in liver and kidney functions in all mycotoxins-treated rats. The studied organs (liver, kidney and spleen) exhibited significant damage, with the most severe alterations observed in the Mix1 and Mix2-treated group in comparison with the groups receiving individual treatment. This indicates that the mixture of AFB1, ALT-Ts and OTA had an enhanced toxic consequence against treated HepG-2 cell line and rats. Our results indicated the synergistic effect of the combined different mycotoxins against HepG-2 human liver cancer cells and male albino rats. This work could help fill in data gaps and enhance risk assessment for human health by addressing some of the possible risks associated with Alternaria toxins